Exploring the Way to Improvemnet in the Cyber Insurance Industry - Cai, Jinxuan (International Journal of Global Economics and Management, 2024)
Cyber insurance is a nascent form of insurance in the digital economy. Its potential for growth and integration within industrial ecosystems in China has garnered increasing interest from academic circles in recent years. China stands to benefit from the promising prospects of cyber insurance, bolstered by national policy support and a dual focus on stimulating both supply and demand. The operational mechanism for establishing uniform norms remains imperfect, and there is a need to clarify the legal attributes of cyber insurance, its operational mechanism, and the types of insurance, as well as to address the unique challenges and issues of cyber insurance from the perspective of the insured to the insured. This paper analyses the characteristics and deficiencies of the primary development stage of China's existing cyber insurance industry based on existing research at home and abroad. It also puts forward suggestions for the improvement of China's cyber insurance industry from the perspective of the internal participant in the cyber insurance industry.